2022
DOI: 10.1111/jcal.12644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contextual interactive healthcare training on caregivers of patients with suspected COVID‐19 infection: Anxiety, learning achievements, perceived support and self‐efficacies during quarantine

Abstract: Background: The contextual and interactive learning research was motivated by the need to enhance the healthcare training effect of caregivers of patients with suspected COVID-19 infection during quarantine. However, there is a lack of effective approaches to integrating mobile contextual learning into interactive learning.Objectives: Therefore, this study developed a mobile augmented reality-integration contextual interactive healthcare training system, and then investigated the effects of the proposed system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(63 reference statements)
0
3
1
Order By: Relevance
“…In contrast to Williams et al, this study found a way to evaluate and reflect the performance of an AI project and to conduct classes efficiently from teachers' perspectives [35]. In contrast to Geng et al's finding that teachers employ design thinking in teaching to address the barrier of resource shortages, beliefs, and redesign of curricula, our results suggest training teachers on AI contextual problem design to help them deal with teaching problems such as solving conflicts peacefully [17].…”
Section: Axial Code 2: Continual Design and Improvementcontrasting
confidence: 75%
See 2 more Smart Citations
“…In contrast to Williams et al, this study found a way to evaluate and reflect the performance of an AI project and to conduct classes efficiently from teachers' perspectives [35]. In contrast to Geng et al's finding that teachers employ design thinking in teaching to address the barrier of resource shortages, beliefs, and redesign of curricula, our results suggest training teachers on AI contextual problem design to help them deal with teaching problems such as solving conflicts peacefully [17].…”
Section: Axial Code 2: Continual Design and Improvementcontrasting
confidence: 75%
“…Previous researchers have pointed out several kinds of design frames from teachers' perspectives regarding innovative lesson design, such as pedagogical frames, knowledge-based design frames, process-based design frames, contextual design frames, idea development frames, perception frames, enactment frames, and institutional frames [7,8,16]. It has been investigated how to teach effectively with the support of design frames [7,13,17].…”
Section: Design Frames From Teachers' Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers often face complex challenges in managing the care of Alzheimer's patients. Mobile apps and platforms offer educational resources, training modules, and information that can empower caregivers with knowledge and skills [27]. This assists them in providing more effective care, managing challenging behaviors, and enhancing the overall wellbeing of the patients they support.…”
Section: Zhaomentioning
confidence: 99%
“…Recently, investigators have conducted studies on the use of technology to improve learners’ ability to use PPE correctly for the protection of themselves and their patients [ 22 , 23 ]. Several studies have investigated the effectiveness of videos for conveying information related to COVID-19 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%